The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fmicb.2019.00441
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Interactions of Pseudomonas aeruginosa With Scedosporium Species Frequently Associated With Cystic Fibrosis

Abstract: Members of the Scedosporium apiospermum species complex are the second most frequently isolated pathogens after Aspergillus fumigatus from cystic fibrosis (CF) patients with fungal pulmonary infections. Even so, the main risk factors for the infection are unrevealed. According to previous studies, bacterial infections might reduce the risk of a fungal infection, but an antibacterial therapy may contribute to the airway colonization by several fungal pathogens. Furthermore, corticosteroids, which are often used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 69 publications
0
26
1
Order By: Relevance
“…Such findings underscore the importance of systems-level approaches that more fully reflect the complexity of these microbiota. Additionally, agonistic and antagonistic interactions among members of the CF airway microbiota can occur, influencing community composition dynamics, as suggested by various reports and confirmed on some microbial species under in vitro conditions [49][50][51][52][53]. While host factors, including genetic background and immune responses, also play important roles in CF pathogenesis, their contribution in shaping respiratory microbiota is not well studied.…”
Section: Host and Therapeutic Factorsmentioning
confidence: 98%
“…Such findings underscore the importance of systems-level approaches that more fully reflect the complexity of these microbiota. Additionally, agonistic and antagonistic interactions among members of the CF airway microbiota can occur, influencing community composition dynamics, as suggested by various reports and confirmed on some microbial species under in vitro conditions [49][50][51][52][53]. While host factors, including genetic background and immune responses, also play important roles in CF pathogenesis, their contribution in shaping respiratory microbiota is not well studied.…”
Section: Host and Therapeutic Factorsmentioning
confidence: 98%
“…Such interactions have been described for Scedosporium spp. and Pseudomonas aeruginosa (46). While direct contact with the bacteria resulted in fungal growth inhibition, the presence of P. aeruginosa could enhance the growth of the fungus when the two microorganisms were cultured "plate to plate" with a physical separation.…”
Section: Pharmacokinetic/pharmacodynamic Parametersmentioning
confidence: 99%
“…SCFM2 was further modified by the addition of p-aminobenzoic acid (PABA), nicotinamide adenine dinucleotide (NAD + ), adenine (ADE), guanine (GUA), xanthine (XAN), and hypoxanthine (HX) to generate SCFM3, as experimental results suggested that these metabolites are more available in CF sputum than in SCFM2 (11). We used PGM was used as the mucin source as it is a cost effective and common replacement of BSM (12)(13)(14).…”
Section: Resultsmentioning
confidence: 99%
“…Pulmonary mucus is a nutritionally distinct environmental niche comprised of mucin, DNA, amino acids, lipids, and micronutrients, including metals (1,2). To study the physiology of microbial pathogens and communities in the unique CF pulmonary environment, a variety of artificial sputum media (ASM) have been developed (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14), and applied to investigate microbial physiology (3,5,(15)(16)(17), biofilm morphology (10,18), antibiotic susceptibility (19,20), and interspecies interactions in the context of CF (21)(22)(23). However, disparate nutrient concentration and bioavailability between ASM formulations may affect microbial growth, metabolism, and virulence (3,7,20,24).…”
mentioning
confidence: 99%